Implementasi digital marketing dalam meningkatkan bisnis UKM (usaha kecil dan mikro) di Kelurahan Makroman Kalimantan Timur - Tikawati, Tikawati; Darmawati, Darmawati; Fadhilah, Nurul; Rahmah, Fitria (Penamas: Journal of Community Service, 2023)
Business demands for the use of technology in the marketing activities of small and medium enterprises have become mandatory to be met. Business competition and increasingly high business creativity require every small and micro business actor to carry out marketing strategies that are adapted to the times. The need for the internet is mandatory in all activities including business activities. Therefore, small and micro business actors must master digital marketing as one of the most effective tools in marketing products and services. This community service activity aims to increase the insight into knowledge, as well as the skills of small and micro business actors in terms of utilizing digital marketing, in this case the mastery of social meda. This activity was attended by 25 small and micro business participants using the seminar method, explanation of power point slides and LCD projectors, sharing experiences and discussions, as well as direct practice of creating social media accounts (business whatsapp, facebook, Instagram, tik-tok). This community service was carried out in Makroman Village, Welcome District, Samarinda City. The results show that several micro-small business groups have been active in implementing social media as a medium for promoting their business, although there are still many people who have not mapped online business accounts with accounts for personal gain. All participants showed great interest and attention in this activity and they have used marketing media through social media as a promotional medium on an ongoing basis.